THE IMPLEMENTATION OF LANGUAGE PROGRAM TO IMPROVE ENGLISH SPEAKING SKILLS FOR ELEVENTH GRADE STUDENTS AT AL-IHSAN BOARDING SCHOOL - Alfayyad, M Rafqi; Hadi, Abdul (English Tadris Department, Tarbiyah and Teacher Training Faculty, Datokarama State Islamic University Palu, 2024)
This study aimed to examine the implementation of the Language Program and the factors influencing its execution in an Islamic boarding school in Pekanbaru. The research employed a qualitative case study approach, utilizing purposive sampling techniques to select participants. Data were collected through interviews with two teachers, a dormitory supervisor responsible for the language section, and a deputy principal in charge of the curriculum section, as well as through observations and focus group discussions involving 10 students. The findings revealed that the implementation of the language program at Al-Ihsan Boarding School was generally effective. The supporting factors included the consistent execution of established programs, the availability of facilities, the role of teachers, the use of teaching materials, media, and strategies. However, several inhibiting factors were identified, such as students' low motivation to use English, limited time, linguistic challenges, and anxiety experienced by some students.